2013
DOI: 10.1128/iai.00778-13
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of arcD in Streptococcus pneumoniae D39 Impairs Its Capsule and Attenuates Virulence

Abstract: The arginine deiminase system (ADS) is associated with arginine catabolism and plays a role in virulence of several pathogenic bacteria. In Streptococcus pneumoniae, the ADS genes exist as a locus consisting of arcABCDT. A recent genome-wide mutagenesis approach revealed that both arcD and arcT are potentially essential in a chinchilla otitis media (OM) model. In the present study, we generated ⌬arcD, ⌬arcT, and ⌬arcDT mutants by homologous recombination and evaluated their infectivity. Our results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…One possible explanation for this hyperattenutation could be the disruption of a secondary function of ArcB that resides outside arginine catabolism. Recently it has been demonstrated that deletion of arcD in S. pneumoniae has a negative impact on pathogenesis independent of its canonical function within the ADI pathway (39). However, given that deletion of arcC in S. pyogenes downstream of arcB was also hyperattenuated in the cutaneous model, the data presented are more consistent with a tissue-specific requirement for citrulline metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…One possible explanation for this hyperattenutation could be the disruption of a secondary function of ArcB that resides outside arginine catabolism. Recently it has been demonstrated that deletion of arcD in S. pneumoniae has a negative impact on pathogenesis independent of its canonical function within the ADI pathway (39). However, given that deletion of arcC in S. pyogenes downstream of arcB was also hyperattenuated in the cutaneous model, the data presented are more consistent with a tissue-specific requirement for citrulline metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…95 A mutation in the gene encoding the arginine transporter ArcD caused a reduction in capsule production and ability to cause OM in a chinchilla model, likely due to differences in the surface association of capsule. 96 A study demonstrated that a laboratory-generated capsular switch led to increased pathogenesis in a chinchilla barotrauma model of AOM. 93 In another barotrauma model of OM, serotype 6C strains showed reduced ability to produce ME disease as compared with serotype 19A isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A bacterial adhesion assay was performed as previously described with slight modification [41, 42]. Briefly, A549 cells were seeded into 24-well tissue culture plates at 2 × 10 5 cells per well and incubated at 37 °C with 5% CO 2 for 24 h before infection.…”
Section: Methodsmentioning
confidence: 99%